Vulnerable young people's experiences of child and adolescent mental health services. Issue 2 (12th June 2017) - Davison, Jo; Zamperoni, Victoria; Stain, Helen J.
Abstract : Purpose: The purpose of this paper is to explore the experiences of vulnerable young people in using a local child and adolescent mental health service (CAMHS). Design/methodology/approach: A mixed methods design was employed in which participants completed the self-report Experience of Service Questionnaire (CHI ESQ) ( n =34), and a subgroup completed individual semi-structured interviews ( n =17). CHI ESQ satisfaction data were also compared with a national data sample provided by the Child Outcomes Research Consortium ( n =621). Findings: Many young people appeared to have a mixed or negative experience of the CAMHS service. They strongly emphasised that feeling listened to, cared for, and supported, in addition to access and continuity of care, are key methods to enhance their experience. They also reported a lack of knowledge and stigma associated with mental health as key barriers to engagement with services more widely. Research limitations/implications: Purposive sampling was used to recruit a carefully defined group of vulnerable young people from one school using a single CAMHS service. Practical implications: A number of recommendations were identified that could enhance the service experience of young people. Originality/value: There is a significant paucity of knowledge regarding young people's views and experiences of CAMHS, especially those with high vulnerability for mental health difficulties. This exploratory study offers methods for capturing the opinions of underrepresented young people to inform future service design.